Characteristics of auditory brainstem response in wild yellow grouper Epinephelus awoara - Zhu, Xiangyu; Zhang, Xinhai; Chen, Mingru; Xu, Xiaomei (Frontiers in Marine Science, 2023)
Auditory brainstem response (ABR) technology is used to set up a fish auditory threshold detection system, and the auditory threshold of wild yellow grouper Epinephelus awoara caught in the Taiwan Strait is studied. The ABRs of 10 wild yellow groupers (TL150-200 mm) to 12 different frequencies of sound stimulation from 100 to 2000 Hz are recorded and analyzed. The results show that the auditory threshold of wild yellow grouper fish increases with the increase of frequency in the frequency of 200-2000Hz. The fish is sensitive to low frequency sound signal of 100-300Hz with the most sensitive frequency of 200Hz, and the auditory threshold is 90 dB re 1μPa. The ABR waveform shows three periods: response period, real hearing period and extension period. In the range of 100-2000Hz, the response time decreases with the increase of frequency at the same sound pressure level. At the same frequency, the response time increases with the decrease of sound pressure level. The first amplitude sound pressure of real hearing period is between 50-150nv, and the real hearing period contains the greatest amplitude. When the greatest amplitude is about 50nv and the next sound pressure level is below 50nv, the sound pressure level is the auditory threshold. The extension period is proportional to the response period.